Mediating Effect of Organizational Learning Capacity on the Relationship between Relational Embeddedness and Innovation Performance in Freight Logistics Service - Pengxia Bai; Qunqi Wu; Qian Li; Chenlei Xue; Lei Zhang (Complexity)
Cooperative innovation has become a critical method for freight logistics firms in supply chain management. The previous study has proved that relational embeddedness (RE) has a positive effect on service innovation performance. However, the influence of organizational learning capacity (OLC) has been widely ignored. This study focuses on explaining the mechanism of OLC on the relationship between RE and innovation performance of freight logistics service (IPFLS). Firstly, a theoretical model is constructed based on Social Network Theory, and four research hypotheses are presented. Secondly, a sample of 236 respondents from freight logistics firms in China is analyzed to test the hypotheses. Finally, several management implications and recommendations are suggested. The research results demonstrate that both RE and OLC have positive effects on IPFLS. Meanwhile, OLC partially mediates the relationship between RE and IPFLS. The findings provide practical guidance for managers to strengthen the relationship with partners and enhance OLC.